Analysis of the Production Process in Increasing the Production Capacity of Red Bricks at UD Alwin, Hilina'a Village, Gunungsitoli District - Ndruru, Ronaldo Syah Putra; Gea, Jeliswan Berkat Iman Jaya; Zai, Kurniawan Sarototonafo; Duha, Tiarni (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the production process in increasing the production capacity of red bricks at UD. Alwin, located in Hilinaa Village, Gunungsitoli District. The focus of the study is directed at the production stages starting from clay processing, molding, drying, to firing, as well as improvement efforts made to increase production capacity. The research method used is a qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the production process implemented by UD. Alwin is still dominated by the use of manual tools and traditional methods. This has an impact on limited production capacity and high dependence on weather conditions, especially in the drying stage. The main obstacles faced are weather factors, limited labor, and minimal modernization of production equipment. However, the synergy between the owner and employees in identifying problems and formulating solutions is a major strength in maintaining business continuity. Overall, improvements in the production process have been proven to have a positive impact on increasing production capacity, although not optimal. Thus, this study concludes that the increase in red brick capacity at UD. Alwin is greatly influenced by the effectiveness of production process management. The recommendations given are the need for innovation in the use of appropriate technology, improving workforce skills, and more efficient work time management to support business desires and competitiveness.